Republikanin i arystokrata. Spotkania J. Q. Adamsa z J. de Maistre’em w Saint-Petersburgu w latach 1809-1814 - Grobis, Jerzy (Acta Universitatis Lodziensis. Folia Historica, 1995)
J. Q. Adams was the first minister of the United States in Russia. Dis diaries are very valuable as the source of knowledge about the court of tsar Alexander the First and the diplomatic life during the stormy days of Napoleonic wars. St. Petersburg in those days gathered the flower of al) european aristocracy who, on russian ground, tried to find any shelter because of danger of the French Revolution and the Napoleonic wars. J. de Maistre as the legate of Sardinia was just among those emigrants. He lived very simply reading many books, but he was homesick. He was interested in ancient philosophy and the european thought. J. Q. Adams was also interested in. that. So these both men started to change their books and opinions. They became more and more closer to each other, but they never become friends. J. Q. Adams, as the man o f the American Revolution, could not agree with the political opinions and with the religious convictions of J. de Maistre. Nowadays J. de Maistre is known an the father of the european conservatism. In J. Q. Adams’s diaries he is described as a great philosopher, an orthodoxal catholic and a politician who glorified on ancient regime. J. Q. Adams admired the erudition of J. de Maistre but did not agree with his political opinions. Perhaps, that is why the writings of J. de Maistre (now in the Adams’s Library, Mass.) were never talked about and quoted in the Adams family.